Irritable bowel syndrome in childhood: treatment in accordance with international guidelines - O.Yu. Belousova (Zaslavsky O.Yu., 2024)
Irritable bowel syndrome (IBS) is diagnosed according to the Rome IV criteria for functional gastrointestinal disorders. It is estimated that 10-15 % of older children and adolescents suffer from IBS. IBS causes abdominal discomfort and pain and can worsen quality of life in children. The article provides an analysis of changes in ideas about pathogenetic mechanisms, approaches to the diagnosis and treatment of IBS in children. Once the diagnosis of IBS is made, it is important to explain to the parents and children that there is no serious underlying disease. This reassurance may be effective treatment in many cases. Lifestyle modifications, stress management, dietary interventions and probiotics may be beneficial in some cases. Although there is limited evidence for efficacy of pharmacological therapies such as antispasmodics, laxatives, and antidiarrheals, they play a positive role in severe cases.